A FIXED POINT APPROACH TO ORTHOGONAL STABILITY OF AN AQ-FUNCTIONAL EQUATIONS IN MODULAR SPACES - El-Fassi, Iz-iddine (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
Abstract. In this paper, we present a ï¬xed point method to prove generalized Hyers-Ulam stability of the following orthogonally additive - quadratic functional equation f(x + ay) = f(x) + a^2f(y) âˆ’( a2 âˆ’ a)/2[f(x + y) âˆ’ f(x âˆ’ y)] where a âˆˆ N âˆ’ 0, 1, in modular spaces.